Implementation Of Disclosure Of Bank Confidentiality In The Effort To Eradicate Money Laundering Crime - Mohammad Fadarisman; Bambang Tri Bawono (Law Development Journal, 2021)
The purpose of this research is to identify and analyze the implementation of bank secrecy disclosure in an effort to eradicate money laundering in the construction of legal certainty and to know and analyze the obstacles faced in the implementation of bank secrecy disclosure in an effort to eradicate money laundering. ) in the perspective of law enforcement. This study uses a sociological juridical approach, which in this case relates to the role of the State Attorney in recovering state financial losses with descriptive analytical research specifications. The data used are primary and secondary data which will be analyzed qualitatively. The research problem was analyzed using the theory of justice and the theory of expediency. The results of the study conclude that the eradication of money laundering in Indonesia will not be effective against law enforcers, both the police, prosecutors, and judges who investigate, prosecute, and examine cases of money laundering crimes, but the bank secrecy provisions as referred to in the Banking Law. Meanwhile, the obstacles faced by law enforcement officers in conducting investigations and investigations of money laundering practices are: 1) Weak provisions for bank secrecy, 2) Bank Indonesia secrecy with exceptions that are limitative and bureaucratic are considered as obstacles, 3) Law Enforcement Officials cannot know fully accurate financial information stored in the bank belonging to the suspect or defendant,